2009
DOI: 10.4103/0255-0857.53201
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics

Abstract: The term "probiotic" was first used in 1965, by Lilly and Stillwell, to describe substances secreted by one organism which stimulate the growth of another. The use of antibiotics, immunosuppressive therapy and irradiation, amongst other means of treatment, may cause alterations in the composition and have an effect on the GIT flora. Therefore, the introduction of beneficial bacterial species to GI tract may be a very attractive option to re-establish the microbial equilibrium and prevent disease. Prebiotic is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
193
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(210 citation statements)
references
References 65 publications
0
193
0
17
Order By: Relevance
“…It is suggested that the mechanisms of improved feeding tolerance may be regulation of intestinal motility, stimulation of intestinal mucosal lactase activity and lowering the intestinal pH (Gupta and Garg, 2009). L. sporogenes produces acids but no gas from fermentation of maltose, mannitol, raffinose, sucrose and trehalose, so this characteristic of the probiotic may be also effective in improving feeding tolerance (De Vecchi and Drago, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the mechanisms of improved feeding tolerance may be regulation of intestinal motility, stimulation of intestinal mucosal lactase activity and lowering the intestinal pH (Gupta and Garg, 2009). L. sporogenes produces acids but no gas from fermentation of maltose, mannitol, raffinose, sucrose and trehalose, so this characteristic of the probiotic may be also effective in improving feeding tolerance (De Vecchi and Drago, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported to have positive effects on the maintenance of human health (Gupta & Garg 2009). Interest in probiotics has gained great significance due to the increasing antimicrobial resistance of bacteria worldwide.…”
Section: Probiotics Biosurfactants Activitymentioning
confidence: 99%
“…3 The presence of probiotic microorganisms in intestinal mucosa can prevent the colonization of pathogens, probably via competitive effects, production of antimicrobial substances, and/or modulation of mucosal immunity. [4][5][6] Shu et al 7 observed that the consumption of probiotic bacteria induced a reduction in diarrhea caused by Escherichia coli toxin in pigs. The authors also observed an increase in phagocyte activity and in levels of IgA antibodies, reducing the mortality caused by E. coli 0157:H7 in mice.…”
Section: Introductionmentioning
confidence: 99%